Optimization of enzymatic extraction process of anthocyanins from blueberry wine residue by response surface method - CHEN Jinqiu, HARDIE Jim, LI Hongyu, ZENG Lingwen (Zhongguo niangzao)
In order to improve the utilization of blueberry wine residue, using cellulase as control, amylase, pectinase, acid protease and neutral protease as the experimental group and anhydrous ethanol as extraction solvent, anthocyanins from blueberry wine residue was extracted. The effects of enzyme addition, extraction time, temperature, and initial pH on anthocyanin extraction yield were investigated by single factor tests, and the enzymatic extraction process of anthocyanins from blueberry wine residue was optimized by response surface tests. The results showed that the optimal enzymatic extraction process of anthocyanins were obtained as follows: amylase addition 0.7%, the ratio of blueberry wine residue and ethanol 1∶100 (g∶ml), extraction temperature 60 ℃, time 40 min, and initial pH 5. Under these optimal conditions, the anthocyanin extraction yield was 0.68 mg/g, which was increased by 20.8% compared with before optimization.